Influence of photooxidation on the lipid profile of rapeseed oil using UHPLC-QTOF-MS and multivariate data analysis. Issue 22 (23rd May 2019) - Wu, Ying; Xu, Feiran; Ji, Shengyang; Ji, Jialu; Qin, Fuyi; Ju, Xingrong; Wang, Lifeng
Abstract : Rapeseed oil, the third most commonly consumed vegetable oil in the world, can easily deteriorate under photooxidative conditions. Abstract : Rapeseed oil, the third most commonly consumed vegetable oil in the world, can easily deteriorate under photooxidative conditions. However, there is no data describing its lipid profile, which provides good information on the stability and quality of the oil. This paper aims to study the lipid composition of rapeseed oil during storage for 12 days under light by ultrahigh-performance liquid chromatography quadrupole time-of-flight mass spectrometry (UHPLC-QTOF-MS). 112 kinds of triacylglycerol (TAG), 13 kinds of diacylglycerol (DAG) and 32 kinds of (phospholipid) PL were identified quantitatively. The total lipid content decreased from 4.14 × 10 8 to 3.21 × 10 8 ng mL −1 . Unsupervised principal component analysis (PCA) and supervised orthogonal partial least square (OPLS) analysis were employed for the characterization of statistically significant differences in identified lipid species, providing better visualization of lipidomic differences between control and experimental samples. The distribution of lipid classes was modified with a decreased proportion of TAG accompanied by the increase of DAG and PLs. Some unique lipid species, such as TG (18:1/18:2/18:2), TG (18:1/18:1/18:1), TG (18:2/22:1/22:1), DG (18:2/18:2), and DG (18:1/18:1) showed great changes and some PA species, including PA (18:2/18:2), PA (18:1/18:2), PA (18:1/18:1) and PA (16:0/18:2), emerged during the last three days of storage. The data can serve as a theoretical basis for the quality assessment of rapeseed oil during storage.